Surface-based characteristics of the cerebellar cortex visualized with ultra-high field MRI - Boillat, Yohan; Bazin, Pierre-Louis; O'Brien, Kieran; Fartaria, Mário João; Bonnier, Guillaume; Krueger, Gunnar; van der Zwaag, Wietske; Granziera, Cristina (NeuroImage (Orlando, Fla.), 2018)
Although having a relatively homogeneous cytoarchitectonic organization, the cerebellar cortex is a heterogeneous region characterized by different amounts of myelin, iron and protein expression profiles. In this study, we used quantitative T1 and T2* mapping at ultra-high field (7T) MRI to investigate the tissue characteristics of the cerebellar gray matter surface and its layers. Detailed subject-specific surfaces were generated at three different cortical depths and averaged across subjects to create averaged T1- and T2*-maps on the cerebellar surface. T1 surfaces showed an alternation of lower and higher T1 values when going from the median to the lateral part of the cerebellar hemispheres. In addition, longer T1 values were observed in the more superficial gray matter layers. T2*-maps showed a similar longitudinal pattern, but no change related to the cortical depths. These patterns are possibly due to variations in the level of myelination, iron and zebrin protein expression. •Quantitative T1 and T2∗ maps reflect the distribution of myelin and iron in the brain.•qT1 and qT2∗ values were mapped onto study-specific cerebellar surfaces.•Both T1 and T2* cerebellar surfaces revealed patterns of parasagittal bands.•T1 values were lower for deeper cortical depths, while T2∗ values did not differ between different cortical depths.